Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamainternmed.2020.3134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sustained-Release Morphine for Refractory Breathlessness in Chronic Obstructive Pulmonary Disease on Health Status

Abstract: IMPORTANCE Morphine is used as palliative treatment of chronic breathlessness in patients with advanced chronic obstructive pulmonary disease (COPD). Evidence on respiratory adverse effects and health status is scarce and conflicting.OBJECTIVE To assess the effects of regular, low-dose, oral sustained-release morphine on disease-specific health status (COPD Assessment Test; CAT), respiratory outcomes, and breathlessness in patients with COPD.INTERVENTIONS Participants were randomly assigned to 10 mg of regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 38 publications
4
92
0
2
Order By: Relevance
“…A DB‐RCT of 4 weeks duration compared slow‐release morphine 10 mg bd versus placebo for relief of dyspnoea in moderate to very severe COPD 58 . Patients had received optimal pharmacological and non‐pharmacological treatment prior, including completion of pulmonary rehabilitation.…”
Section: New Developments In Copdmentioning
confidence: 99%
“…A DB‐RCT of 4 weeks duration compared slow‐release morphine 10 mg bd versus placebo for relief of dyspnoea in moderate to very severe COPD 58 . Patients had received optimal pharmacological and non‐pharmacological treatment prior, including completion of pulmonary rehabilitation.…”
Section: New Developments In Copdmentioning
confidence: 99%
“…Metaanalyses of clinical trials provide evidence that, in combination with usual care including disease-modifying therapies and non-pharmacological interventions, regular low dose opioids may safely reduce moderate to severe chronic breathlessness due to advanced illness; with the majority of evidence relating to morphine. 5,6 The most recent published trials 7,8 did not show benefit for the study populations as a whole, but a significant number of participants had less severe chronic breathlessness (for whom a response is less likely 9 ). However, sub-group analyses of participants with moderate to severe chronic breathlessness in both trials showed reduction in breathlessness compared with placebo, reaching statistical significance in one.…”
Section: Introductionmentioning
confidence: 98%
“…3,4 In addition, although expert opinion considers lowdose full MORs helpful in the treatment of refractory dyspnea, their benefit has been difficult to demonstrate in randomized controlled settings. 5,6 One reason for this may be that assessment of dyspnea through questionnaires may be underestimating the impact of treatment as patients may increase their activity level to reach their previous breathlessness severity level if the treatment is helpful; it has been suggested that more objective measures, such as use of accelerometers to measure changes in activity, may be better suited to assess treatment effects. 7,8 Nevertheless, patients seen in palliative care settings often suffer from comorbid pain, also raising concerns about need for higher opioid doses (and hence side effects) than might suffice to treat isolated dyspnea.…”
Section: Introductionmentioning
confidence: 99%